IoT-based indoor access control and monitoring: a case study from the containment measures of the COVID-19 pandemic. (28th April 2022) - Andrade, Sergio Henrique; Negrão, Rogério; Fernandes, Micael; Costa, Fernando; Seruffo, Marcos César Da Rocha
The COVID-19 pandemic has led many serving environments to seek solutions to control people's access and avoid crowding in order to contain its spread, and to ensure the health and safety of users. Given the various current solutions, this paper presents a monitoring system that shows, in real-time, via web, the status of people in closed environments. It uses internet of things (IoT) techniques for data interconnections and electronic components - NodeMCU board and proximity sensors - to monitor the entrance and exit of people in an enclosed environment, providing the statistics through an IoT platform (application) that can be installed in a mobile device (smartphone). This study highlights a low-budget system, shows the implementation of IoT platforms in the development of prototypes and the tests carried out in the academic service office.